Aboutthe meaning of the notion of Indifferenz on pages 28-37of Die Weltalter - Rojas Jiménez, Alejandro (Claridades. Revista de filosofía, 2014)
On pages 28-37 Schelling specifies how the notion of indifference should be thought. He distinguishes different ways of thinking the notion of indifference to end up defending it must be conceived from the idea of alternation à la Anaximander, which is an alternative process of partial dominance between the opposing forces of expansion and contraction (productive and own will) which leads to a continuous process by which the will is free. In this ongoing process of adopting of form we distinguish three stages: the stage of quiet contemplation, the stage of separation and unification, and the stage of freedom. We will use at the end the notion of instant and delight to understand the process.